The behavior of a discrete spectrum at a one-dimensional perturbation - Syrovatsky, A. N. (Reports of the National Academy of Sciences of Ukraine, 2016)
The case of the overlay of a discrete part of the spectrum of a linear operator on an absolutely continuous part at a one-dimensional perturbation is studied.